Analysis of nominal data - multi-way contingency table - Stanimir, Agnieszka (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
Presented in this paper the method of graphical presentation of the relationship between nominal variables and their categories gives the opportunity for an extensive diagnosis of dependence variables. Correspondence analysis and mosaic plots are based on the same grounds, i.e. contingency table or multi-way contingency table. Correspondence analysis can be used in the study of relationships between two or more nominal variables without limiting the number of categories. In the case of many variables, the multidimensional contingency table is used very often. Only the difficulty of construction of such a table and the combined variables can affect the decision of a researcher about the validity of using this solution. For mosaic plots the situation is different. These graphs represent very well the relationships between two categories of nominal variables with few categories. The introduction of another variable to the study, which is described by two or three categories, is also not too problematic, and the graph is easy to interpret. However, if in a multi-way contingency table variables are a combination of several primary variables, described with many categories, the mosaic plot is no longer as clear as the projection made in correspondence analysis.
Mathematical Economics, 2011, Nr 7 (14), s. 229-240
Keywords: nominal data; multi-way contingency table; mosaics displays; correspondence analysis